"A Rape Is a Rape, Regardless of What the Victim Was Doing at the Time": Detective Views on How "Problematic" Victims Affect Sexual Assault Case Processing. (March 2020) - O'Neal, Eryn Nicole; Hayes, Brittany E.
Research finds that "problematic" victim behaviors—for example, alcohol consumption—influence sexual assault case outcomes. Questions remain, however, regarding officer perceptions of what constitutes a problematic victim and how these victims complicate case processing. Indeed, most case processing research has relied on quantitative methods and inquiry into officer attitudes has primarily relied on the use of vignettes. Using data from in-depth interviews with 52 Los Angeles Police Department sex crimes detectives, we examine attitudes toward problematic victims. Overall, we aim to determine whether rape culture beliefs and efforts to operate in a "downstream orientation" influence detective views regarding victims who have been deemed problematic.